The Impact of Inflation on the Stock price Index Amman's Stock Exchange case study during the period (2000 - 2016) - Kasoa, Raged; kasser, Kamel (Latakia University Journal - Economic and Legal Sciences Series, 2018)
This study showed a relationship between inflation and stock index prices in Amman's financial market during the period (2000-2016). Through the use of several tests using (Eviews8) statistical program. where it tests( stability time series) by using kpss test and conduct a normal distribution test using (Jarque-Bear) test As well as a linear regression between the dependent and independent variable using the least squares method OLS. This study concluded that the static inflation string variable at the level while the stock price index to Amman's financial market chain was static at the first differences, and also the study variables of the financial Amman market are not subject to normal distribution, and through the regression equation using the least squares method OLS show a statistically significant positive relationship between inflation and stock index prices at Amman's Stock Exchange. أثر التضخم على مؤشر أسعار الأسهم دراسة حالة سوق عمان المالي خلال الفترة (2000 - 2016) أظهرت هذه الدراسة العلاقة بين التضخم ومؤشر أسعار الأسهم في سوق عمان المالي خلال الفترة (2000-2016). من خلال استخدام عدة اختبارات باستخدام البرنامج الإحصائي (Eviews8). حيث تم اجراء اختبار السكون (استقرار السلاسل الزمنية) وذلك عن طريق اختبار kpssوإجراء اختبار التوزيع الطبيعي باستخدام اختبار (Jarque-Bear)، وكذلك إجراء الانحدار بين المتغير التابع والمتغير المستقل باستخدام طريقة المربعات الصغرى OLS. وخلصت هذه الدراسة إلى عدة نتائج من أهمها: أن سلسلة متغير التضخم ساكنة عند مستواها، في حين أن سلسلة مؤشر أسعار الأسهم لسوق عمان المالي ساكنة عند الفروق الأولى، وكذلك لا تخضع متغيرات الدراسة لسوق عمان المالي للتوزيع الطبيعي, ومن خلال معادلة الانحدار باستخدام طريقة المربعات الصغرى OLS تبين وجود علاقة ذات دلالة إحصائية موجبة بين التضخم ومؤشر أسعار الأسهم لسوق عمان المالي.